2023
DOI: 10.1186/s12916-023-02768-z
|View full text |Cite
|
Sign up to set email alerts
|

Rare mutation-dominant compound EGFR-positive NSCLC is associated with enriched kinase domain-resided variants of uncertain significance and poor clinical outcomes

Abstract: Background Compound epidermal growth factor receptor (EGFR) mutations are less responsive to tyrosine kinase inhibitors (TKIs) than single EGFR mutations in non-small cell lung cancer (NSCLC). However, the detailed clinical characteristics and prognosis of various compound EGFR mutations remain to be elucidated. Methods We retrospectively studied the next-generation sequencing (NGS) data of treatment-naïve tumors from 1025 NSCLC patients with compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Multiple studies have consistently shown that patients with compound EGFR mutations tend to exhibit reduced sensitivity to TKI therapies compared with those with single EGFR mutations [ 6 , 7 , 23 , 24 ]. Furthermore, emerging evidence suggests that the specific types of compound EGFR mutations may be linked to different treatment response patterns [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have consistently shown that patients with compound EGFR mutations tend to exhibit reduced sensitivity to TKI therapies compared with those with single EGFR mutations [ 6 , 7 , 23 , 24 ]. Furthermore, emerging evidence suggests that the specific types of compound EGFR mutations may be linked to different treatment response patterns [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that individuals with compound EGFR mutations may show reduced responsiveness to TKI therapies compared with those with single mutations [ 6 9 ]. Additionally, different treatment efficacies have been associated with different types of EGFR compound mutations [ 10 , 11 ]. While first-generation EGFR -TKIs could be a useful treatment option, recent studies suggest considering afatinib and osimertinib for patients with compound EGFR mutations, depending on their specific cases [ 12 , 13 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Matched white blood cells from each patient were sequenced in parallel to remove sequencing artifacts, germline variants, and clonal hematopoiesis. Copy number variant (CNV) analysis was conducted by adjusting copy number values according to sample ploidy using FACETS [23,24]. Structural variants (SVs) were detected by FACTERA using default parameters [25].…”
Section: Methodsmentioning
confidence: 99%
“…Copy number variant (CNV) analysis was conducted by adjusting copy number values according to sample ploidy using FACETS [23,24]. Structural variants (SVs) were detected by FACTERA using default parameters [25].…”
Section: Data Processing and Mutation Callingmentioning
confidence: 99%
See 1 more Smart Citation